Model Picosatellite Design for Energy Harvesting and Telemetry Data Transmission through RF Communication - Songul, Gamze; Yalman, Alper; Ilginoglu, Ayse; Gokce, Anil; Koculu, Omer Eren Can; Kirli, Ahmet; Koru, Ahmet Taha; Tufekci, Celal Sami (IEEE, 2015)
In this paper, we present the design and the production of an artificial picosatellite named NuD-34 in order to compete in CanSat 2014 which is an annual student design-build-launch competition. According to the rules of the competition, satellites have to perform some tasks such as obtaining telemetry information, harvesting energy, communicating to a ground station, and landing within an egg safely without breaking. All of the mechanical and electrical subsystems are described in detail to perform those tasks while satisfying the budget, the dimensional and the mechanical constraints. In this study a satellite is developed and realized under the rules of CanSat Competition 2014, which essentially aims to promote innovative space solutions and to improve the current systems.
Keywords: picosatellite; CanSat; harvesting energy; recovery system of satellite; telemetry transmission; Engineering